The Distinct Biological Effects of 6-Hydroxy-L-Nicotine in Representative Cancer Cell Lines - Paula Alexandra Postu; Razvan Stefan Boiangiu; Marius Mihasan; Alexandru Bogdan Stache; Adrian Tiron; Lucian Hritcu (Molecules)
6-hydroxy-L-nicotine (6HLN) is a nicotine (NIC) derivative with proven therapeutic potential in neurodegenerative disorders. Here, the impact of 6HLN on cell growth, migratory behavior, and inflammatory status of three different cancer cell lines (A549, MCF7, and U87) and two normal cell lines (16HBE14o and MCF10A) was investigated. In silico analyses were conducted to evaluate the binding affinity of 6HLN to nicotinic receptors (nAChRs) containing α9 and α5 subunits. The obtained in silico data revealed that 6HLN might act on the cholinergic system. Interestingly, the in vitro data showed the compound has cancer-stimulatory effects in U87 glioblastoma cells and cancer-inhibitory effects in MCF7 breast cancer cells. In A549 lung cancer cells, no changes were detected upon 6HLN administration. More importantly, 6HLN appears not to be deleterious for normal cells, with the viability of 16HBE14o pulmonary cells and MCF10A mammary cells remaining unchanged.